Pregnancy, prescription medicines and the potential risk of herb-drug interactions: a cross-sectional survey - James S. McLay; Naila Izzati; Abdul R. Pallivalapila; Ashalatha Shetty; Binita Pande; Craig Rore; Moza Al Hail; Derek Stewart (BMC, 2017)
Abstract Background Pregnant women are routinely prescribed medicines while self-medicating with herbal natural products to treat predominantly pregnancy related conditions. The aim of this study was to assess the potential for herb-drug interactions (HDIs) in pregnant women and to explore possible herb-drug interactions and their potential clinical significance. Methods A cross-sectional survey of women during early pregnancy or immediately postpartum in North-East Scotland. Outcome measures included; Prescription medicines use excluding vitamins and potential HDIs assessed using Natural Medicines Comprehensive Database. Results The survey was completed by 889 respondents (73% response rate). 45.3% (403) reported the use of at least one prescription medicine, excluding vitamins. Of those taking prescription medicines, 44.9% (181) also reported concurrent use of at least one HNP (Range 1-12). A total of 91 different prescription medicines were reported by respondents using HNPs. Of those taking prescription medicines, 44.9% (181) also reported concurrent use of at least one HNP (Range 1-12). Thirty-four herb-drug interactions were identified in 23 (12.7%) women with the potential to increase the risk of postpartum haemorrhage, alter maternal haemodynamics, and enhance maternal/fetal CNS depression. Almost all were rated as moderate (93.9%), one as a potentially major (ginger and nifedipine) and only one minor (ondansetron and chamomile). Conclusion Almost half of pregnant women in this study were prescribed medicines excluding vitamins and minerals and almost half of these used HNPs. Potential moderate to severe HDIs were identified in an eighth of the study cohort. Healthcare professionals should be aware that the concurrent use of HNPs and prescription medicines during pregnancy is common and carries potential risks.